Sintering behavior of 3D printed barium titanate composite scaffolds for bone repair (Transactions on Additive Manufacturing Meets Medicine, 2020)
Additive manufacturing of novel biomaterials with additional stimulating functions represents a promising strategy for bone repair. In this study, a systematic investigation of the necessary thermal post-treatment of 3D printed barium titanate composite ceramics to achieve the desired mechanical properties for bone regeneration is presented. The maximum sintering temperature was varied from 1320 °C to 1380 °C in 10 K intervals. After sintering, the samples were systematically characterized with respect to their porosity and mechanical properties. Specimens sintered at 1380 °C exhibit a considerably densified microstructure and improved mechanical integrity compared to specimens sintered at lower temperatures.
Keywords: biomaterial; bone repair